2011
DOI: 10.1111/j.1600-0889.2011.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based off-line aerosol measurements at Praia, Cape Verde, during the Saharan Mineral Dust Experiment: microphysical properties and mineralogy

Abstract: A B S T R A C TA large field experiment of the Saharan Mineral Dust Experiment (SAMUM) was performed in Praia, Cape Verde, in January and February 2008. This work reports on the aerosol mass concentrations, size distributions and mineralogical composition of the aerosol arriving at Praia. Three dust periods were recorded during the measurements, divided by transitional periods and embedded in maritime-influenced situations. The total suspended particle mass/PM 10 /PM 2.5 were 250/180/74 μg/m 3 on average for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 77 publications
(117 reference statements)
2
33
0
Order By: Relevance
“…It has now been shown that, when immersed in water, the feldspar component nucleates ice much more efficiently than the other main minerals that make up typical desert dust (Atkinson et al, 2013;Augustin-Bauditz et al, 2014;O'Sullivan et al, 2014;Niedermeier et al, 2015;Zolles et al, 2015). This is an important finding as it has been demonstrated that feldspar is a common component of aerosolized mineral dusts (Glaccum and Prospero, 1980;Kandler et al, 2009Kandler et al, , 2011Atkinson et al, 2013;Perlwitz et al, 2015). Feldspar particles in the atmosphere tend to be larger than clay particles and so will have shorter lifetimes in the atmosphere, however aerosol modelling work has suggested that feldspar particles can account for many observations of INP concentrations around the world (Atkinson et al, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…It has now been shown that, when immersed in water, the feldspar component nucleates ice much more efficiently than the other main minerals that make up typical desert dust (Atkinson et al, 2013;Augustin-Bauditz et al, 2014;O'Sullivan et al, 2014;Niedermeier et al, 2015;Zolles et al, 2015). This is an important finding as it has been demonstrated that feldspar is a common component of aerosolized mineral dusts (Glaccum and Prospero, 1980;Kandler et al, 2009Kandler et al, , 2011Atkinson et al, 2013;Perlwitz et al, 2015). Feldspar particles in the atmosphere tend to be larger than clay particles and so will have shorter lifetimes in the atmosphere, however aerosol modelling work has suggested that feldspar particles can account for many observations of INP concentrations around the world (Atkinson et al, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…Kandler et al (2011b) observed the presence of 4 size distribution modes during the SAMUM-2 campaign, in January of 2008, at Praia airport, using a Differential Mobility Particle Sizer (DMPS) for the size range 26-800 nm and an Aerodynamic Particle Sizer (APS) for the aerodynamic size range of 570 nm-10 μm. The finest mode of the volume size distribution was found for D p of 200-300 nm and was attributed to sulfate.…”
Section: Size Distributionsmentioning
confidence: 99%
“…An intensive 1 month field experiment run in Praia during January 2008 integrated in the SAMUM-2 campaign revealed PM 10 values of the order of 29 μg.m −3 , during transport of maritime air masses, and of 223 μg.m −3 , during dust events with air masses transported directly from Africa (Kandler et al, 2011b); the mass ratio between PM 10 and PM 2.5 did not present a significant variation during the field experiment, with an average of 2.67, not very different from our annual average ratio of 2.53.…”
Section: Pm Concentrationsmentioning
confidence: 99%
“…The Anti-atlas mountains was also 25 suggested as a source of micronutrients to the North East Atlantic Ocean by Chavagnac et al (2007). In off-line filters collected at Praia Cabo Verde, Kandler et al (2011b) reported illite/kaolinite ratio of between 1:2 and 1:4 during winter transport of dust to Cabo Verde from coastal Mauritania and Mali respectively. In continuous long term measurements of elemental composition, Patey et al (2015) reported seasonal variation in Al content which was attributed to seasonal changes in dust transport, and reported illite as the most abundant.…”
mentioning
confidence: 99%
“…The traditional method for reporting the composition of aerosol particles involves the classification of particles into compositional groups using a variety of elemental ratios and boundary rules e.g Kandler et al (2007Kandler et al ( , 2011b ;Young et al (2016).…”
mentioning
confidence: 99%